2021
DOI: 10.29399/npa.27175
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits and Social Responsiveness: The Relationship Between Autistic Traits and Comorbid Psychiatric Symptoms in Adolescents With Anorexia Nervosa

Abstract: Introduction: It is known that patients with anorexia nervosa (AN) display social difficulties like social responsiveness and high levels of autistic behaviors such as rigidity, narrow interests of food and weight; however it is not clear whether they have comorbid Autism Spectrum Disorders (ASD) or it is about acute phase of illness. In this study it is aimed to investigate autistic traits and social responsiveness in adolescents with AN. Methods: Study group was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…It is well-established that anorexia nervosa can be associated with autistic features, such as difficulties in social cognition, emotion regulation, and abnormal attention processing ( 4 ). Previous studies have reported that female adolescents diagnosed with anorexia nervosa exhibit lower social communication skills and higher autistic characteristics ( 33 ). Approximately one-fifth of individuals with anorexia nervosa are reported to display autism-related features, which can manifest as challenges in communication, social analysis, and theory of mind ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that anorexia nervosa can be associated with autistic features, such as difficulties in social cognition, emotion regulation, and abnormal attention processing ( 4 ). Previous studies have reported that female adolescents diagnosed with anorexia nervosa exhibit lower social communication skills and higher autistic characteristics ( 33 ). Approximately one-fifth of individuals with anorexia nervosa are reported to display autism-related features, which can manifest as challenges in communication, social analysis, and theory of mind ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AN have been shown to have smaller social support groups (22), demonstrate diminished responsiveness and sensitivity to social cues (23,24), and can be more negative in their interpretation of social situations (25), particularly when feeling ostracized (26). Research investigating the presence of social deficits in AN and illness outcomes found lower effectiveness of treatment and longer AN duration when social impairments were present (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The consensus among researchers is that the presence of interpersonal difficulties in AN negatively impacts treatment outcomes (24,35,36). Given a large component of success in AN treatment is dependent on therapeutic relationship quality (37,38), deficits in socialisation and possible poor relationship quality may hinder the therapeutic relationship and, by extension, the effectiveness of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation